FORMULATION AND EVALUATION OF HERBAL ORAL EMULGEL CONTAINING PSIDIUM GUAJAVA LINN. LEAVES EXTRACT (A PREVENTIVE ORAL CARE PREPARATION) - AKBAL AHMAD,; NIRANJAN, ABADHESH KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The present research work is based to establish the formulation and evaluation of herbal oral emulgel containing extracts of powdered Psidium guajava Linn. leaves extract. Methods: The guava leaves were collected and extracted by cold maceration process using different solvents, further ethanolic extract was used for the emulgel preparation. Emulsion and gel phase were prepared separately and mixed together in ratio of 1:1. Results: Different formulations ere developed and evaluated for the physical appearance, pH, homogeneity, spreadability, viscosity, extrudability, antibacterial activity, and in vitro skin permeability studies. In all formulated emulgel containing P. guajava Linn. Leaves, extract F2 formulation gives all satisfactory results as in discuss in this paper. Conclusion: Overall, concluded that the extract might contain anti-bacterial properties and further tests are required to prove for oral care activity using other in vivo or in vitro techniques.